A clinical study to determine the efficacy of 7 ppm dexmedetomidine as an adjuvant to 2% lignocaine in infraorbital nerve block. Issue 9 (November 2016) - Khandaitkar, S.; Kolte, V.; Shenoi, S.R.; Budhraja, N.
Abstract: Dexmedetomidine is a selective alpha-2-adrenoceptor agonist used as an adjuvant for regional anaesthesia. We studied its efficacy as an adjuvant to lidocaine in infraorbital nerve block in 90 patients divided equally into three groups. The first group (control) was given 2% lidocaine 2 ml only, the second, 2% lidocaine 2 ml with dexmedetomidine 14 μg peripherally (peripheral group), and the third, 2% lidocaine 2 ml peripherally with dexmedetomidine 14 μg systemically (systemic group). Onset of anaesthesia, duration of action, blood pressure, oxygen saturation, and heart rate were evaluated. The mean (SD) onset of action was faster in the peripheral group (185 (39.02) seconds) than in the others (control: 261.67 (67.02); systemic: 217.37 (34.86) seconds). The duration of action was longer in the peripheral group (124.87 (19.75) minutes) than in the others (control: 70.43 (13.62); systemic: 88.83 (20.63) minutes). Differences in blood pressure, oxygen saturation, and heart rate measured at different intervals were not significant. The addition of 7 mg/L dexmedetomidine to lidocaine perineurally speeds up the onset of action and prolongs the duration of anaesthesia.